THE ROLE OF INTERNATIONAL LAW IN ENSURING MONGOLIA’S NATIONAL SECURITY - Bayartogtokh, Nergui; Dashzeveg, Batbayar; Delgermaa, Paashka (International Journal of Innovative Technologies in Social Science, 2026)
This article examines the role of international law in ensuring Mongolia’s national security from the perspective of small-state security policy. The contemporary international security environment is no longer limited to traditional military threats, border disputes, and armed conflict. It is increasingly shaped by multidimensional factors such as human rights, information and cyber domains, economic and energy security, environmental risks, migration, transnational crime, and hybrid threats. Under such conditions, the legal system for ensuring national security must develop not only within the scope of domestic legislation but also in close connection with the generally recognized principles and norms of international law, international treaties, multilateral institutional mechanisms, international courts and dispute settlement systems, and legal regimes relating to human rights and collective security. As a landlocked small state located between two great powers, with relatively limited demographic, economic, and material military resources, Mongolia has a particular need to use international law as a strategic instrument of national security. International law plays a crucial role in safeguarding Mongolia’s independence, sovereignty, territorial integrity, inviolability of borders, human rights, multi-pillared foreign policy, international cooperation, peace support operations, disarmament commitments, and nuclear-weapon-free status. The study applies document analysis, systemic legal analysis, comparative legal analysis, small-state security policy analysis, and theoretical synthesis of international law. The findings suggest that international law performs five key functions within Mongolia’s legal system for ensuring national security: first, a guarantee function for protecting independence, sovereignty, and territorial integrity, second, a normative function for strengthening human security, human rights, democratic governance, and the rule of law, third, a strategic function for supporting the external security of a small state through multilateral cooperation, international organizations, diplomacy, and legal mechanisms, fourth, a cooperation function for addressing non-traditional and transnational threats, and fifth, a regulatory function for guiding domestic legal and institutional reform. The article concludes that Mongolia needs to strengthen the incorporation of international legal norms into domestic legislation, assess the implementation of international treaties, enhance professional capacity in international law, introduce international legal risk analysis into national security policymaking, and increase Mongolia’s active contribution to the development and implementation of international law.